Efficacy of Triphala Rasayana – A Review - Gangwar, Akanksha; Yadav, S S (International Research Journal of Ayurveda & Yoga, 2023)
Introduction: Even after increasing urbanization, Ayurveda remains the classical and comprehensive part of ancient medicine system for well-being promotive diseases, preventive, and revival approach for human body. Conventionally, rasayana-based formulation is utilized in different types of diseases as well as to restore the health of an individual. Triphala Rasayana as mentioned in Ayurvedic classics comprised of Amalaki, Vibhitaki, and Haritaki with variable proportions. It is classified as “Tridoshika Rasayana” and is one of the most well-studied Ayurvedic drugs which show its various pharmacological activities. Reason behind being called as Rasayana is that it acts as the rejuvenator and immunomodulator, which provides numerous health benefits to any individual. Materials and Methods: Various references regarding the triphala, rasayana, and triphala rasayana have been gone through verse by verse, especially in chikitsasthana of Charak Samhita and Dravya Guna along with other significant material from relevant resources to get the detailed information regarding them. Results: Various medicinal attributes of Triphala rasayana include antioxidant, anti-cancerous, antidiabetic, antimicrobial, and immunomodulator. Many clinical studies found Triphala Rasayana to be effective against diabetes, constipation, and obesity also. Because of the in numerous health benefits of Triphala rasayana, Acarya Caraka has mentioned that is any individual practices this recipe continuously for 1 year, he/she would be able to cherish a long life of 100 years, free from ageing and diseases. Conclusion: Triphala Rasayana is recognized as one of the most well-studied Ayurvedic Rasayanas. It has been utilized in various traditional medicine systems. Conventionally, rasayana-based drugs are utilized in different kinds of diseases. Many clinical studies found Triphala Rasayana to be effective against diabetes, constipation, and obesity also. Hence, it can be inferred that Triphala Rasayana is a pack of wonders with numerous health benefits which helps in the restoration of all the age groups.